UPAYA PENCAPAIAN STANDAR KETUNTASAN BELAJAR MINIMAL (SKBM) MELALUI PEMBELAJARAN KOOPERATIF MODEL STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - Nurcholish Arifin Handoyono (Jurnal Taman Vokasi, 2015)
The purpose of this study is to increase the minimum mastery standard in automotive electrical systems repairing matter with subject applying Student Team Achievement Division (STAD) model cooperative learning. This study used a classroom action research whitch was conducted in two cyles, each eycle consisted of four phases: planning, implementation, observation, dan reflection. The data were analyzed descriptively. The result proved that teaching learning process using STAD model cooperative learning increased the minimum mastery standard of students. Before applying STAD model cooperative learning, none passed the minimum mastery standard. After applying STAD model cooperative learning, there are advancement in term of the number of students passing the standard 48,48% in the first cycle and 87,88% in the second cycle. The average score reached 71,48 and 81,83 in the first and the second cycle. Therefore, this study concludes that STAD cooperative model increased the minimum mastery standard in automotive electrical systems repairing subject.